2020
DOI: 10.1016/j.jsxm.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Visual Conformity with Affirmed Gender or “Passing”: Its Distribution and Association with Depression and Anxiety in a Cohort of Transgender People

Abstract: Background: Visual conformity with affirmed gender (VCAG) or "passing" is thought to be an important, but poorly understood, determinant of well-being in transgender people. VCAG is a subjective measure that is different from having an inner sense of being congruent with one's gender identity. Aim:We examined the frequency and determinants of VCAG and explored its association with mental health outcomes in a cohort of transgender adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…While the current study was not sufficiently powered to detect differences between gender identity subgroups, it is possible that gender nonconformity is experienced differently by binary as opposed to nonbinary transgender people. While social stigmatization of gender norm divergence might negatively affect both groups equally, it is possible that, for nonbinary people, being read as gender nonconforming might also affirm their identity and might be considered as “passing” (Rood et al, 2017; To et al, 2020). Future studies could benefit from further examining how gender nonconformity might both inhibit and promote mental health in nonbinary people by studying “passing” as well as gender nonconformity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the current study was not sufficiently powered to detect differences between gender identity subgroups, it is possible that gender nonconformity is experienced differently by binary as opposed to nonbinary transgender people. While social stigmatization of gender norm divergence might negatively affect both groups equally, it is possible that, for nonbinary people, being read as gender nonconforming might also affirm their identity and might be considered as “passing” (Rood et al, 2017; To et al, 2020). Future studies could benefit from further examining how gender nonconformity might both inhibit and promote mental health in nonbinary people by studying “passing” as well as gender nonconformity.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could benefit from further examining how gender nonconformity might both inhibit and promote mental health in nonbinary people by studying “passing” as well as gender nonconformity. Furthermore, as participants who underwent gender-affirming health care interventions could experience less gender nonconformity than their counterparts (To et al, 2020; Wernick et al, 2019), future studies looking into the role of gender nonconformity as a potential moderator could benefit from including this variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported less dissatisfaction for non-binary people [ 36 ] whilst in our sample there is a tendency of higher dissatisfaction for non-binary adolescents. These different results can be attributed to various factors such as timing and status of social and medical transition, reality of life [ 10 ], social environment, extent of passing [ 37 , 38 ] or location and year of survey [ 39 ]. Accordingly, caution should be exercised in making generalized statements and more research is needed to gain more knowledge on correlates of gender differences in body dissatisfaction among transgender adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has also been applied to understand other conditions such as mental illness (To et al, 2020), HIV (Lacombe-Duncan et al, 2020;Mbeda et al, 2020) and socioeconomic situations (Pescosolido & Martin, 2015). However, a definition of stigma applied to challenges faced by TGD people globally, particularly in the context of healthcare access, is unclear.…”
Section: Introductionmentioning
confidence: 99%